Palliative Psychiatry for Patients With Severe and Persistent Mental Illness: A Survey on the Attitudes of Psychiatrists in India Compared to Psychiatrists in Switzerland - Stoll, Julia; Mathew, Anju; Venkateswaran, Chitra; Prabhakaran, Anil; Westermair, Anna Lisa; Trachsel, Manuel (Frontiers in Psychiatry, 2022)
Objectives: Palliative psychiatry is a new approach for the care of patients with severe and persistent mental illness (SPMI) which systematically considers biological, psychological, social, and existential factors of care. To assess the attitudes of psychiatrists in India towards palliative psychiatry for patients with SPMI and to compare these to the attitudes of psychiatrists in Switzerland. Methods: In an online survey, data from 206 psychiatrists in India were collected and compared with data from a previous survey among 457 psychiatrists in Switzerland. Results: Psychiatrists in India generally considered it very important to prevent suicide in SPMI patients (97.6%). At the same time, they considered it very important to reduce suffering (98.1%) and to ensure functionality in everyday life (95.6%). They agreed that palliative psychiatry is important for providing optimal care to SPMI patients without life-limiting illness (79.6%) and considered palliative psychiatry as indicated for patients with SPMI (78.2%). By contrast, curing the illness was considered very important by only 39.8 % of respondents. Relative to psychiatrists in Switzerland, psychiatrists in India were significantly more concerned about preventing suicide and less willing to accept a reduction in life expectancy, even at the expense of quality of life in patients with severe and persistent schizophrenia and recurrent major depressive disorder. At the same time, they were significantly more likely to advocate palliative psychiatry. Conclusion: Most of the participating psychiatrists in India agreed that palliative psychiatry can be indicated for patients with SPMI. The comparison with psychiatrists in Switzerland highlights the need to take account of cultural differences in future studies of this kind. In summary, this study shows the potential of palliative psychiatry as a genuine biopsychosocio-existential approach which systematically integrates biological, psychological, social, and existential factors of care.